Field study 1 : the learner's development and environment - Lucas, Maria Rita D. (Quezon City, Philippines : Lorimar Publishing, 2010)
As forints objectives, this revised workbook on Field Study 1 aims to align teacher education with the CHED-prescribed new teacher education curriculum that is reflective of the National Competency-Based Teacher Standards. This workbook closely adheres to the Experiential Learning Courses Handbook, a project of the Teacher Education Council (TEC), Department of Education.
Field Study 1 The Learner's Development and Environment 1 -- FS 1 Episode 1 The School as a Learning Environment 4 -- FS 1 Episode 2 The Learner's Characteristics and Needs 14 -- FS 1 Episode 3 Classroom Management and Learning 22 -- FS 1 Episode 4 Individual Differences and Learner's Interaction (focusing on differences in gender, racial, religious backgrounds) 32 -- FS 1 Episode 5 Individual Differences and Learner's Interaction (focusing on Different Levels of Abilities) 41 -- FS 1 Episode 6 Home School Link 49
Keywords: EDUCATION -- PHILIPPINES